3D-characterization of deuterium distributions in zirconium oxide scale using high-resolution SIMS - Li, K; Aarholt, T; Liu, J; Hulme, H; Garner, A; Preuss, M; Lozano-Perez, S; Grovenor, C (Elsevier, 2018)
In pressurised water reactors (PWRs), fuel rods are clad with zirconium alloy tubes chosen for their low neutron capture cross section and good oxidation resistance. Understanding cladding-water corrosion reactions at 280–350 °C and the correlated hydrogen pickup into these Zr alloys is crucial to the safe operation of PWRs and to increasing the burnup of the fuel. Here we describe a method based on 3D mapping by high resolution SIMS to measure the distribution of deuterium in oxidised Zircaloy-4 alloy samples. Two analysis directions, depth-profiling and cross-sectional, were used to ensure we understand possible imaging artefacts during sputtering of the complex microstructure in these samples. The topography of the sputtering carter and sputtering rate have been calibrated by Focused Ion Beam (FIB)/Scanning Electron Microscopy (SEM) analysis. The deuterium diffusion coefficients at 360 °C is calculated suing the depth profile in both samples. The results show that the 3D deuterium distribution can be successfully measured in isotopically spiked samples, but that care has to be taken to understand the effect of deuterium outgassing and surface diffusion during Cs+ primary ion bombardment, which results in a degraded lateral resolution, which distorts the apparent deuterium distribution. The detection method in this paper can be a useful tool in the analysis of the distribution of hydrogenic species in zirconium fuel cladding materials in service, and can also provide other engineering materials